Local social mission of higher education: The case of Eastern European rural faculties. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2011)
In the past decade, a new issue has emerged in the scientific and political discourse on the mission of higher education institutions.